The Effect Of Ceo Popularity On Firm Performance With Free Cash Flow As A Moderating Variable - Nasrudin, Nasrudin; Utami, Eva Yuniarti; Apriadi, Deni; Harahap, Irwan Musriza; Djami Rane, Melvin Krisdiana; Berutu, Edi Putra (Universitas Pahlawan Tuanku Tambusai, 2024)
This research is a quantitative study with an explanatory approach, namely an approach that supports previous research as the main reference for building a foundation for the research being carried out. The data used in this study are secondary data that researchers obtained from credible sources such as the Indonesia Stock Exchange from 2013 to 2023. The data were analyzed using the smart PLS 4.0 analysis tool. The result in this article show that the CEO Popularity variable can have a positive relationship direction and a significant influence on Company Performance because the P-Values ​​are positive and below the significance level of 0.05, namely 0.009. This is because a polished CEO can make negotiations easier, the company profile is increasingly well-known, and ultimately can improve Company Performance. These results are in line with research. In the next row, it can be concluded that the Free Cash Flow variable can moderate the influence of the CEO Popularity variable on Company Performance because the P-Values ​​are positive and below the significance level of 0.05, namely 0.000, which is more significant than direct testing of 0.09. Thus, it can be concluded that the first and second hypotheses in this article can be proven and accepted.